2023
DOI: 10.1002/bies.202300042
|View full text |Cite
|
Sign up to set email alerts
|

ISG15: A link between innate immune signaling, DNA replication, and genome stability

Abstract: Interferon stimulated gene 15 (ISG15) encodes a ubiquitin‐like protein that is highly induced upon activation of interferon signaling and cytoplasmic DNA sensing pathways. As part of the innate immune system ISG15 acts to inhibit viral replication and particle release via the covalent conjugation to both viral and host proteins. Unlike ubiquitin, unconjugated ISG15 also functions as an intracellular and extra‐cellular signaling molecule to modulate the immune response. Several recent studies have shown ISG15 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 138 publications
(238 reference statements)
0
3
0
Order By: Relevance
“…Among these, OAS1 also amplifies the type I IFN pathway and expression of genes that promote immune evasion ( 49 ). In addition, ISG15 links the DNA damage response to regulation of innate immunity ( 50 ). Along these lines, we found that MUC1-C regulates expression of guanylate-binding protein 1 (GBP1), which is activated by chronic inflammation and confers treatment resistance (refs.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, OAS1 also amplifies the type I IFN pathway and expression of genes that promote immune evasion ( 49 ). In addition, ISG15 links the DNA damage response to regulation of innate immunity ( 50 ). Along these lines, we found that MUC1-C regulates expression of guanylate-binding protein 1 (GBP1), which is activated by chronic inflammation and confers treatment resistance (refs.…”
Section: Resultsmentioning
confidence: 99%
“…Engagement of such structures leads to activation of an ISG transcriptional program that culminates in the modulation of chromatin states and replication fork stability. In effect, the model suggests that this circuitry, which evolved as an antiviral mechanism has been coopted to effect surveillance of the replication fork 64 (Fig.8F).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the MRN complex regulates fork progression, altering the protein landscape on nascent DNA by a cGAS-STING-TbK1 pathway-dependent modulation of Interferon stimulated gene 15 (ISG15) [32,33].…”
Section: Mrn Complex In Dsbs and Replication Stress Handlingmentioning
confidence: 99%